Long-term trend of the ionospheric F2 layer peak height at a southern low latitude station - Ortiz de Adler, Nieves del Carmen (2002)
The trend of the peak height of the ionospheric F2 layer, hmF2, during three solar cycles (1957?1986) at Tucuman (26.9°S, 65.4°W), station located at the southern peak of the equatorial anomaly, has been estimated. hmF2 was calculated from M(3000), foE and foF2 records at 12 LT using Bilitza equation, which has been tested with real height values obtained from more than 200 rescaled ionograms. The anomalies, hmF2A, calculated as the deviation of experimental hmF2 values from that calculated assuming a linear dependence between hmF2 and the sunspot number, were estimated. The cumulated periodogram of hmF2A indicates a non-random behavior, within a 95% confidence level. After removing the effect of solar cycle variations and periodicities of less than 5 years, hmF2A shows a mean decrease of 0.2 km/yr (6 km in 30 years). A decrease of 14% in the maximum ionospheric electron density, NmF2, was also observed at the same station for the same period in a previous work of the authors. The lowering of hmF2 and NmF2 observed at Tucuman, are greater than that expected from the theory of a sinking of the upper atmosphere, due to a cooling in the thermosphere produced by the increase in CO2 concentration.